Comparative analysis of the functional outcome of distal femur fractures treated with Distal Femur locking Plate versus Dynamic Condylar Screw. - Arvind Kumar, Bodla; Kumar, P.A. Shravan; Omer, Faisal Bin; Cherukuri, Nagesh; Reddy, Lakkireddy Maheshwar (International Journal of Health and Clinical Research, 2021)
Back ground:Fractures of distal femur are more common in high velocity injuries and occur in middle aged men and old age women. Most fractures were comminuted. DISTAL LOCKING FEMUR PLATE[DLFP] appears to be technically an ideal implant for comminuted distal femoral fractures with proper physiotherapy produced excellent results. DYNAMIC CONDYLAR SCREW[DCS]appears to be relatively easy construct to fix in the distal femur fracture, however bulky implant, mandatory of 2 to 4cm Intact femoral condyle for lag screw insertion and varus collapse of medial fragment in case of comminuted fractures, made this good implant only for Muller typeA.Objective - To evaluate the advantages, disadvantages and possible complications associated with fixation of distal femur fracture with distal femur locking plate versus dynamic condylar screw.Material and methods :This is a prospective, randomised comparative study done over 24 patients in NIMS hospital, Hyderabad during study period of 1year (2018-2019) in orthopaedic department.Results:In Type A fractures DCS produced better functional results when compare to DLFP in our study.Infection, knee stiffness and mal alignment of fractures were the common complication we encountered in our series in both DLFP and DCS, which could be tackled by surgical expertise, meticulous soft tissue handling, judicious use of antibiotics and vigorous early knee mobilization.Conclusion: DISTAL LOCKING FEMUR PLATE [DLFP] produces better results and appears to be a good method of choice for management of fractures of distalfemur.